Effect of Dietary Supplementation of Melon (Citrallus Lanatus) Seed Oil on the Growth Performance and Antioxidant Status of Growing Rabbits - Singh, A.S; Alagbe, J.O; Sharma, S; Oluwafemi, R.A; Agubosi, O.C.P (Research Parks Publishing LLC, 2021)
This study was carried out to determine effect of dietary supplementation of melon (Citrallus lanatus) seed oil (WMO) on the growth performance and immune response of growing rabbits. Thirty six (36), 5-6 weeks weaner rabbit of mixed breed and sex with an average weight of 435 g – 438 grams were randomly divided into four (4) treatments of nine rabbits per group and each rabbit served as a replicate in a completely randomized design (CRD). The experiment lasted for 12 weeks and all other management practices were strictly observed. Basal diet was formulated according to the nutrient requirements of rabbit according to NRC (1977). Treatment (T1) were fed basal diet with 0 % WMO, T2, T3 and T4 were fed basal diet supplemented with WMO at 0.2 %, 0.4 % and 0.6 % respectively. Results obtained were used to examine the average daily weight gain (ADWG), average daily feed intake (ADFI), feed: gain, mortality, activities of superoxide dismutase (SOD), glutathione-S-transferase (GST), reduced glutathione (GSH) and malonyldialdehyde (MLA). ADWG, feed: gain and mortality were significantly different (P˂0.05) among the treatments. ADFI increased as the level of WMO increases, though not at a significant level (P˃0.05). Highest mortality was recorded among animals in T1 (1.00 %), none was recorded in the other treatments (P˂0.05). Activities of SOD, GST, GSH and MLA were significantly (P˃0.05) influenced by WMO. It was concluded that dietary supplementation of WMO up to 0.6 % enhanced growth performance, improved feed: gain and had no negative effect on the antioxidant parameters of rabbits, it is safe and could be used to bridge the gap between food safety and production.